POTENTIAL LEAF CORN AS A SOURCE OF NATURAL DYES AND STABILITIES DURING DRYING POWDER USING BINDER MALTODEKSTRIN - Sri Hardjanti (Jurnal Penelitian Saintek, 2008)
Leaves katuk (Sauropus Androgynus- (L) Merr) is a leaf that can be used as a dye in food, but its use is less practical, therefore it is done by processing leaf katuk extracted and then made into powder. The research variables of katuk leaf powder were made with the addition of maltodectin at variation concentration 4%, 6%, 8%, and drying temperature 80 and 900C. The leaf powder obtained obtained katuk analyzed chemical properties (water content, chlorophyll content), physical properties (color, rehydration) and sensory properties (favorite level). The results showed that the addition of maltodextrin on katuk leaf extract powder tended to have no effect on physical properties (color and rehydration), chemical properties (moisture content, chlorophyll content) but more maltodextrin addition, leaf katuk leaf extract produced less favorable. The drying temperature of katuk leaf extract powder significantly influences chlorophyll content and color intensity on katuk leaf extract powder. The leaf extract powder of katuk is most preferable at 900 C drying temperature with the addition of 4% maltodextrin. Powder of katuk leaf extract has characteristics: water content 5.64% wb, chlorophyll content (0.83% db), Redness color 0.65, Yellowness 8.90, Blueness 2.75; rehydration 1.19 minutes.